Struktur Dan Makna Sufiks ~Gatai Dalam Kalimat Bahasa Jepang - Lina Rosliana; Fida Nurrany Lathifah (IZUMI, 2019)
(Title: Structure and Meaning of Suffix ~Gatai in Japanese Sentences) suffix ~gatai is a suffix that attached to verbs. This research aims to describe the structure and meaning of suffix ~gatai. The data which is used is obtained from the websites, such as yourei.jp, kotonoha.gr.jp, and other sites that contained research topics. The data were collected by observation method and writing technique. Then for data analysis using agih method. The results of the analysis are presented by the informal method which explained with simple words. Based on the results of the analysis, suffix ~gatai can be attached to 3 categories of verbs (1) kanyouku or idiom, (2) ninshiki or cognitive verbs, and (3) hatsugen or verbal verbs. 2 meanings contain suffix ~gatai in Japanese sentences, (1) cannot be realized or something can't happen, and (2) not accepting an agreement.   gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor